De afectos y preceptos: Espinosa y lo político - Lomba, Pedro (ENDOXA, 2002)
Starting from the apparent paradox presented, on the one hand, by denouncing the sensibilities of hope and fear as negative and enslaving and, on the other, determining their political use as absolutely necessary for the establishing of rationality in public life, this article hopes to investígate and so clarify the relationship between sensibility and rationality in Spinoza’s philosophy of inmanence. This relationship, and above all a certain equilibrium between the two terms, is essential in order to define politics such as Spinoza conceived it.